Situation Report: Romania, 7 July 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Aftermath of UN Voting Egyptian Newspaper Criticizes Romania National Conference of Chemical Workers Ceausescu Touring Bucharest Region Soviet-Romanian Trade Miscellaneous